Acasta sulcata akanthosa, new replacement name for Acasta sulcata spinosa - Perreault, Ray T. (Zootaxa, 2016)
Acasta sulcata spinosa Daniel, 1955 has been discovered to be a junior homonym of Acasta spinosa Hiro, 1939. As both names were originally described in the genus Acasta, ICZN (International Commission on Zoological Nomenclature) Article 57.2 defines A. sulcata spinosa as a primary junior homonym, even though it is of subspecific nature.